Insulin Signaling in Arthritis - Tripolino, Cesare; Ciaffi, Jacopo; Pucino, Valentina; Ruscitti, Piero; van Leeuwen, Nina; Borghi, Claudio; Giacomelli, Roberto; Meliconi, Riccardo; Ursini, Francesco (Frontiers in Immunology, 2021)
Arthritis is burdened by an increased risk of metabolic disorders. Cytokines and other mediators in inflammatory diseases lead to insulin resistance, diabetes and hyperlipidemia. Accumulating evidence in the field of immunometabolism suggests that the cause-effect relationship between arthritis and metabolic abnormalities might be bidirectional. Indeed, the immune response can be modulated by various factors such as environmental agents, bacterial products and hormones. Insulin is produced by pancreatic cells and regulates glucose, fat metabolism and cell growth. The action of insulin is mediated through the insulin receptor (IR), localized on the cellular membrane of hepatocytes, myocytes and adipocytes but also on the surface of immune cells, such as macrophages, T-cells, dendritic cells. In murine models, the absence of IR in T-cells coincided with reduced cytokine production, proliferation, and migration. In macrophages, defective insulin signaling resulted in enhanced glycolysis affecting the responses to pathogens. In this review, we focalize on the bidirectional cause-effect relationship between impaired insulin signaling and arthritis analyzing how insulin signaling may be involved in the aberrant immune response implicated in arthritis and how inflammatory mediators affect insulin signaling. Finally, the effect of glucose-lowering agents on arthritis was summarized.